Distribution of Phytolacca americana in a coastal sand dune - Byeong-Mee Min (Journal of Ecology and Environment)
This study examined the main factors affecting the distribution of Phytolacca americana , an exotic plant species in Korea, in coastal sand dunes. The areas examined from June 2004 to February 2006 were in Sindusagu where was located on Sindu-ri, Wonbuk-myen, Taean-gun, Chungcheongnam-do. The vegetation, sediment properties, sizes and ages of Robinia pseudoacacia, P. americana and Pinus thnunbergii and spatial distribution of P. americana were assessed. Firstly, correlation coefficients (CC) between P. americana ’s root biomass and sediment properties were not significant. Secondly, of the four community types, P. americana was not in the mixed herbaceous community and its density was the highest in the P. thunbergii−R. pseudoacacia and R. pseudoacacia community The Poisson distribution analysis revealed the distribution of P. americana to be severely clumped. The root biomass of P. americana and the basal area of R. pseudoacacia were significantly correlated, but the CCs between P. thunbergii and other two species were not significant. The ages of P. americana and R. pseudoacacia in a quadrat were significantly correlated. Thirdly, P. americana’s ages in a quadrat were mostly similar to each other. Therefore, the spatial distribution of P. americana was largely influenced by R. pseudoacacia but not by the sediment properties, and plants in a narrow area were concurrently germinated.